Saccharomyces cerevisiae var. boulardii—Fermented Beverages: Health Benefits, Safety Considerations, and Technological Challenges Across Fruit, Dairy, and Cereal Matrices - Hadeel Edkaidek; Divakar Dahiya; Poonam Singh Nigam (Beverages, 2026)
Fermented beverages are increasingly recognized as promising vehicles for delivering probiotics and bioactive compounds; however, their functionality cannot be explained solely by microbial properties, as it is strongly shaped by interactions between the microorganism, the food matrix, and processing conditions. This review critically synthesizes evidence across fruit-, dairy-, and cereal-based fermented beverage systems, with particular attention to the fragmented and often difficult-to-compare nature of the available literature. Although Saccharomyces cerevisiae var. boulardii (S. boulardii) demonstrates notable tolerance to gastrointestinal and processing-related stresses and has been associated with immunomodulatory and gut-health benefits, the translation of these attributes into consistent beverage functionality remains highly matrix dependent. Evidence derived from in vitro, animal, and clinical studies suggests potential health benefits; however, differences in strains, fermentation conditions, beverage composition, and analytical approaches complicate direct comparisons and may partly explain the variability observed among reported outcomes. Beyond biological performance, important challenges remain regarding stability, ethanol production, sensory acceptance, safety considerations, and industrial implementation. Current evidence indicates that beverage composition and processing conditions are major determinants of S. boulardii performance and may partly explain the variability observed among studies. The review further highlights current knowledge gaps and identifies priorities for the development of next-generation functional beverages based on S. boulardii fermentation.